OP93 Adiposity and cardiometabolic risk in White British and Pakistani origin children: skinfold and blood pressure measurements of 1563 reception year children in the Born in Bradford prospective cohort study. (2nd September 2014) - West, J; Fairley, L; Lennon, L; O'Connell, C; Wright, J; Brierley, S; Lawlor, DA
Abstract : Background: Tackling the growing problem of childhood obesity is a public health priority. Over a fifth of children in England start school overweight or obese and prevalence rates are markedly higher among South Asian children. The National Child Measurement Programme (NCMP) provides valuable height and weight data to monitor trends in body mass index (BMI) in English primary schools. However, there is increasing evidence that for a given BMI South Asian children have greater total and central adiposity than White British children and are potentially more metabolically sensitive to body fat. It would therefore be beneficial to collect measures of size (beyond height and weight) that can provide estimates of body fat and contribute to a better understanding of growth and future cardiometabolic risk in South Asians. We examined the skinfold thickness and blood pressure of children participating in the Born in Bradford (BiB) cohort study who entered reception year in September 2012. Methods: 3730 BiB children were eligible for the reception year 2012/13. Information was sent to parents 8 weeks prior to the scheduled measurements with an 'opt out' consent form should they wish to withdraw their child from the measurements. Using data provided by Bradford Education and Learning we were able to match 2541 (68%) BiB children to their school. School nurse teams visited 134 (of 143) schools between March and May 2013 and collected triceps and subscapular skinfold thickness and blood pressure measurements from 2350 children. Of these, 719 were of White British and 844 of Pakistani origin. Results: Pakistani children had a lower BMI (mean difference -0.42 95% CI -0.59, -0.24kg/m 2 ) and lower triceps skinfold thickness (mean difference -1.49 95% CI -1.79, -1.19mm) than white British children but higher subscapular thickness (mean difference 0.41 95% CI 0.23, 0.58mm). They also had higher systolic (mean difference 0.46 95% CI -0.70, 1.63 mmHg) and diastolic blood pressure (mean difference 2.92 95% CI 1.69, 4.13 mmHg) than white British children. Conclusion: These are preliminary findings that suggest there are ethnic differences in BMI, central adiposity and blood pressure at age 4–5 in white British and Pakistani origin UK children. These measurements will be repeated for reception years 2013/14 and 2014/15 to include all BiB children and will be matched to NCMP data. Collectively these measures will help us estimate and understand body fat in children known to be at particularly high risk of both obesity and future cardiometabolic disease.